2020
DOI: 10.20524/aog.2020.0483
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors is associated with a higher risk of pneumonia in cirrhotic patients: a systematic review and meta-analysis

Abstract: Background Proton pump inhibitors (PPIs) are commonly prescribed for cirrhotic patients. However, the use of PPIs in these patients may increase the risk of bacterial infection. The current study aimed to investigate the risk of developing pneumonia among cirrhotic patients exposed to PPIs. Methods A literature search was independently conducted by 2 investigators using the MEDLINE and EMBASE databases up to September 2019. To be eligible, a study had to be an observational (cohort, case-control or cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…In total, we identified 6241 articles, scrutinised 375 full‐text articles, and included 132 eligible articles (3.52%) for preliminary data extraction ( Figure S1). After the selection criteria for the overlapping meta‐analyses were applied, 61 articles were ultimately selected for evidence synthesis 6–8,31–88 . Agreement between reviewers for eligibility of articles was excellent (κ statistic = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…In total, we identified 6241 articles, scrutinised 375 full‐text articles, and included 132 eligible articles (3.52%) for preliminary data extraction ( Figure S1). After the selection criteria for the overlapping meta‐analyses were applied, 61 articles were ultimately selected for evidence synthesis 6–8,31–88 . Agreement between reviewers for eligibility of articles was excellent (κ statistic = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicate that patients with liver cirrhosis are prone to bacterial infections 24,25 because of their impaired immune status, the increased use of invasive procedures, and alterations in the enteric flora. 26,27 For example, Hermos et al 10 showed that use of PPI would increase the risk of CAP by 1.80-fold when compared with non-PPI use in liver disease patients. The pooled analysis of Wongtrakul et al 27 found that cirrhotic patients with a history of PPI use had a significantly higher risk of developing pneumonia than those without PPI use, with a pooled risk ratio of 1.36 (95% CI = 1.00-1.85; I 2 = 47%).…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
“…26,27 For example, Hermos et al 10 showed that use of PPI would increase the risk of CAP by 1.80-fold when compared with non-PPI use in liver disease patients. The pooled analysis of Wongtrakul et al 27 found that cirrhotic patients with a history of PPI use had a significantly higher risk of developing pneumonia than those without PPI use, with a pooled risk ratio of 1.36 (95% CI = 1.00-1.85; I 2 = 47%). However, in our meta-analysis, use of PPI was not associated with CAP in liver disease populations.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
“…New articles on contemporary topics such as PPI safety are regularly added to the global medical literature, which may make it difficult to sum- With this letter, we would like to expand on the work of Salvo et al by mentioning six more recent meta-analyses that were published after their search date. [3][4][5][6][7][8] (Table 1) Several additional adverse effects of PPIs have been evaluated such as increased risk of hepatocellular carcinoma, pancreatic cancer, congenital malformations, and complications in patients with cirrhosis including spontaneous bacterial peritonitis, pneumonia and hepatic encephalopathy.…”
Section: Letter: Mind the Gap -Search And Publication Date Of Systematic Reviews And Meta-analysismentioning
confidence: 99%